Metode Pembelajaran pada Pendidikan Sains untuk Meningkatkan Pendidikan Karakter: Analisis Bibliometrik pada Publikasi 2020-2025 - Zuhdi, Rasyid; Karenina, Aziza; Putri, Winda Rachman; Usnia, Andyta Ma’rifatul; Febrian, Andika; Fattahillah, Nuris (Jurnal Kridatama Sains dan Teknologi, 2025)
The study aims to determine the publication map for the period 2020-2025 related to science learning methods as character education, particularly articles published in journals indexed by Scopus, Crossref, and Google Scholar. The research questions are as follows: (1) How are science learning methods as character education viewed from the publication map? (2) What is interesting for academics regarding science learning methods as character education? (3). What topics are frequently written about in publications related to science learning methods as character education? This study analysed 1,101 articles using the keywords ‘education methods, science education, character education.’ Thematic areas were identified using keyword analysis. The analysis and visualisation process used Publish or Perish and VOSviewer. The study shows that science learning methods as character education have been a trend over the past five years. The keyword visualisation presents 8 clusters: (1) institution; (2) technology; (3) management; (4) local wisdom; (5) outcome; (6) COVID; (7) student character; and (8) child. Bibliometric mapping analysis can provide information related to the development patterns of publications in the field of science education methods for character education. These findings serve as a valuable foundation for future research: 1) The need for holistic and in-depth research on STEAM in science education; and 2) The need for research focused on areas that are still under-explored, such as: (1) integrating character education; (2) blended learning; and (3) local wisdom.